Effect of Phosphogypsum on the Properties of Portland Cement. (2017) - Islam, G.M. Sadiqul; Chowdhury, Fazlul Habib; Raihan, Muhammad Tanveer; Amit, Shishir Kumar Sikder; Islam, Mohammad Rafiqul
Abstract: Use of industrial by-products as construction material can help to achieve sustainability in this industry. Phosphogypsum, a by-product in phosphoric acid manufacturing process, produced in bulk quantity especially from the fertilizer industry, typically used as a supplementary fertilizer for soil treatment. Alternatively, disposal of these materials in the form of landfill also need huge land area although environmental hazard concern from these activities has been raised by researches. The material has therefore, tried to incorporate in cement manufacturing considering its sustainable use. Phosphogypsum could be used as a substitute of natural gypsum in the production of Portland cement to control the hydration reaction rate of cement. In this study, raw phosphogypsum was collected from a local fertilizer industry. Properties of phosphogypsum were evaluated and then the effect of various level phosphogypsum addition (2, 5, 10 and 15 percent by weight of cement) with Portland cement clinker was investigated. The raw material was treated to remove additional water and impurity by washing, air drying and oven drying. Both treated and untreated materials were used in experimental work. Setting time, flow and compressive strength behavior of the prepared paste, mortar and concrete samples were evaluated to find an effective percentage of phosphogypsum to be used in Portland cement manufacturing. By evaluating properties of cement paste, mortar and concrete it was concluded that 5-10% phosphogypsum addition in cement clinker gave good results. In general, the processing of phosphogypsum by washing and drying gave better performance in all the media.